Do You Know How People Who Are Blind Cross Streets? Mentally Stepping into Another's Shoes Through Imitation. (March 2022) - Arsal, Güler; Suss, Joel; Ward, Paul; Eccles, David W.
Introduction: The objective of this study is to investigate the extent to which sighted persons understand thought processes of persons who are visually impaired (i.e., those who are blind or have low vision). The investigation focused on a street-crossing task.Method: Participants were 15 visually impaired persons and 21 sighted persons. The sighted group included 6 orientation and mobility (O&M) specialists and 15 individuals who represent the sighted public and have infrequent interactions with people with visual impairments. Participants provided verbal reports of their thought processes associated with a street-crossing scenario twice, once as a "non-pretender" and once as a "pretender." In the non-pretender role, participants verbalized their thinking in line with their actual state of sightedness. In the pretender role, participants with visual impairments pretended that they did not have any visual impairments, whereas sighted participants pretended that they were blind. Transcribed data were analyzed using thematic analysis, resulting in three themes with 14 subthemes. The genuine responses of visually impaired participants and the imitated responses of the sighted participants were compared using proportions of the subthemes.Results: Fisher's exact z tests demonstrated that out of the 14 subthemes, the visually impaired participants' proportions were (a) similar to those of sighted O&M specialists in 10 subthemes and (b) different from those of the other sighted participants in seven subthemes. Participants verbalized fewer thoughts when describing sighted navigation than when describing navigation as a person with visual impairment.Discussion: Sighted persons with infrequent social interaction with people who are visually impaired seem to be less successful at "pretending to be blind, " indicating that they may have difficulties in adopting the perspective of people with visual impairments.Implications for Practitioners: Sighted O&M specialists develop an understanding of the cognitive processes of people who are visually impaired through training and contact. Other professionals that support these individuals (e.g., technology designers) could benefit from developing such an understanding and immersing themselves in the social life of people with visual impairments.